"A Writer More Than . . . a Child": A Longitudinal Study Examining Adolescent Writer Identity. (January 2018) - Lammers, Jayne C.; Marsh, Valerie L.
This article reconsiders theoretical claims of identity fluidity, stability, and agency through a longitudinal case study investigating one adolescent's writing over time and across spaces. Qualitative data spanning her four years of high school were collected and analyzed using a grounded theory approach with literacy-and-identity theory providing sensitizing concepts. Findings uncovered how she laminated identity positions of perfectionism, expertise, risk taking, and learning as she enacted her passionate writer identity in personal creative writing, English classrooms, an online fanfiction community, and theater contexts. Using "identity cube" as a theoretical construct, the authors examine enduring elements of a writer's identity and the contextual positioning that occurs when youth write for different audiences and purposes. Findings suggest that adolescents approach writing with a durable core identity while flexibly laminating multiple sides of their identity cube, a reframing of identity that has implications for literacy-and-identity research.